Analisis perubahan sifat fisis (viskositas, kerapatan, tegangan permukaan dan koefisien laju penurunan suhu) minyak kelapa (coconut oil) terhadap beberapa kali pemanasan - Khusnul Khotimah; Supriyanto Supriyanto; Adrianus Inu Natalisanto; Asmaidi Asmaidi (Progressive Physics Journal, 2022)
The purpose of this study was to ascertain the impact of repeated heating of coconut oil on the value of viscosity, density (mass density), surface tension, and the coefficient of temperature reduction rate (Newton cooling constant). The coconut oil sample used was the result of my own production. The heating repetition was carried out at most five times with a peak temperature of 90oC. The physics quantities were respectively determined by the methods of the falling ball, the directly measuring the mass and volume with the measuring cylinder, the raising fluid in a capillary tube, and the Newton cooling.From this study, it was found that there was an effect of repeated heating of coconut oil on the value of viscosity, mass density, surface tension, and the Newton cooling constant. This effect is indicated by the presence of a functional relationship between the heating test and the value of the four physical quantities. The relationship between heating repetition and viscosity is a quadratic function, the relationship between heating repetition and mass density is a linear function, the relationship between heating repetition and surface tension is a quadratic function, and the relationship between heating repetition and Newton cooling constant is a quartic function. The four functional relationships are empirical equations that state the laws of nature in a certain heating range and can be used as material for further studies to reveal the physical mechanisms that build them, including determining the general equations that unite them.